Intramolecular Metal Exchange Reaction Promoted by Thiol Ligands - Yangfeng Li; Man Chen; Shuxin Wang; Manzhou Zhu (Nanomaterials, 2018)
The synthesis of an alloy nanocluster that is atomically precise is the key to understanding the metal synergy effect at the atomic level. Using the Ag2Au25(SR)18 nanocluster as a model, we reported a third approach for the metal exchange reaction, that is, intramolecular metal exchange. The surface adsorbed metal ions (i.e., Ag) can be exchanged with the kernel metal atoms (i.e., Au) that are promoted by thiol ligands. The exchanged gold atoms can be further stripped by the thiol ligands, and produce the AgxAu25−x(SR)18− nanocluster.